2023
DOI: 10.3390/molecules28072894
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Contrast-Enhanced Ultrasonography with Phosphatidylserine Microbubbles to Detect Placental Inflammation in Rhesus Macaques

Abstract: The ability to comprehensively monitor physiological and detect pathophysiologic processes early during pregnancy can reduce maternal and fetal morbidity and mortality. Contrast-enhanced ultrasound (CEUS) is a non-invasive imaging technology that utilizes the acoustic detection of microbubbles to examine vascular spaces. Furthermore, microbubbles conjugated to specific compounds can focus studies on precise physiological pathways. We hypothesized that CEUS with phosphatidylserine microbubbles (MB-PS) could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Women with PE have a heightened inflammatory state with elevated pro-inflammatory cytokines and chemokines, both systemically and in the placenta [ 120 , 160 ]. Studies in rodents and non-human primates have provided evidence of mechanistic links between maternal inflammation and PE [ 120 , 122 ]. Lipopolysaccharide-induced inflammation in pregnant rats showed that inflammation was associated with deficient trophoblast invasion and spiral artery remodeling [ 120 ].…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
See 2 more Smart Citations
“…Women with PE have a heightened inflammatory state with elevated pro-inflammatory cytokines and chemokines, both systemically and in the placenta [ 120 , 160 ]. Studies in rodents and non-human primates have provided evidence of mechanistic links between maternal inflammation and PE [ 120 , 122 ]. Lipopolysaccharide-induced inflammation in pregnant rats showed that inflammation was associated with deficient trophoblast invasion and spiral artery remodeling [ 120 ].…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
“…In addition, inflammation increased the maternal mean arterial pressure and was associated with structural changes in the kidney and proteinuria, as is found in PE [ 120 ]. Wilson et al demonstrated increased syncytiotrophoblast inflammation in a testosterone-induced primate model of PCOS using a novel contrast-enhanced ultrasound technique [ 122 ].…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
See 1 more Smart Citation